Students’ Dropout in Higher Education: A Study of Ghodaghodi Multiple Campus - Joshi, Dinesh Raj (Contemporary Research: An Interdisciplinary Academic Journal, 2024)
Despite the significant importance of higher education, student dropout is an issue of global importance that affects students, their families, labor organizations, universities, government agencies and therefore the countries` economy. Although varied definitions, share of students who did not complete a higher education program within the theoretical duration plus added additional years is termed as dropout. OECD member countries statistics indicates on an average approximately one third of university students` do not complete their degree. This study was conducted at Ghodaghodi Multiple Campus, a QAA certified public institute of Kailali aims to explore the causes of dropout using phenomenological research design. In-depth interview was taken with four purposively sampled dropped out students form the campus. The result shows individual, economic, job related, lack of motives to study, marriage, family responsibility causes, lack of job market, waste of time, theory based curriculum, failed in multi years, not attended at examination are found the major causes of student dropout. All the ethical consideration is taken in the study including informed consent. It is suggested to conduct gender wise study on student dropout at the campus.